Influence of Mn on nanobainite formation kinetics and austenite retention in Al-added medium-Mn steels subjected to hybrid isothermal annealing - Mateusz Morawiec; Jarosław Opara; Adam Skowronek; Alireza Kalhor; Aleksandra Kozłowska; Anna Wojtacha; Adam Grajcar (Journal of Materials Research and Technology)
This study investigates the bainite transformation kinetics, microstructural evolution, and mechanical properties of Al-alloyed 3MnNb and 4MnNb multiphase steels subjected to a novel hybrid heat treatment. Dilatometric analysis revealed that bainite formation in the 3MnNb steel initiates more rapidly during isothermal holding, while the 4MnNb steel exhibits accelerated transformation kinetics in later stages, resulting in distinct final bainite fractions. Thermodynamic calculations, including T0 curves, underscore the roles of Mn and Al in modifying the Gibbs free energy landscape and influencing the potential for nanobainite formation. Microstructural characterization identified a lath-type ferritic matrix comprising bainite, retained austenite (RA), and, in some cases, fresh martensite. Lower intercritical annealing temperatures (IATs) favored the formation of coarse ferrite laths and residual martensite, whereas higher IATs promoted microstructural refinement. Although 3MnNb achieved 10–15 % nanobainite, further transformation was limited by the stability of RA and sluggish carbon diffusion at 200 °C. In contrast, the 4MnNb steel displayed enhanced grain refinement, increased hardness, and a higher fraction of stabilized RA, which impeded the progression of nanobainite formation.